Design of 2x6 Butler Matrix for Smart Antennas - Vats, Mudita; Mishra, Arpana; Rai, Mayank; Choudhary, Shilpa (International Journal of Engineering and Technology, 2018)
In this paper a 2x6 butler matrix is designed forswitched beam smart antenna array. This work describes system design and optimization which is based on the elimination of some component (such as: crossover, phase shifter) which are used in basic structure of butler matrix generally and utilization of the output ports of hybrid coupler to make it 10log (1/3) dB coupler. This design increased the number of ports at the output of beam forming network array and miniaturized the area of butler matrix circuit. Proposed model is designed for ISM band of frequency with well accepted simulation results. This model is quite suitable in microwave devices as a low cost, high performance beam forming network in wireless communication system.Â Â